Biological characteristics of energy conversion in carbon fixation by microalgae. (December 2021) - Zeng, Jing; Wang, Zhenjun; Chen, Guobin
Abstract: CO2 -fixation by microalgae can be regarded as a biological process of energy conversion with CO2 and H2 O in microalgae cells in the sunlight. The study of the biological intrinsic characteristics of energy conversion is helpful to reveal the high-efficiency carbon fixation mechanism of microalgae. Firstly, the CO2 emission control technology and the external influencing factors are summarized in this paper, which have laid the foundation for researching the internal biological intrinsic characteristics of carbon fixation by microalgae. Based on photosynthetic reactions, in-situ reaction experiments, hydrodynamic simulations and metabolic networks have been integrated to analyze the biological intrinsic characteristics of carbon fixation by microalgae. The collation of representative studies on theory and quantitative calculation methods reveals that free energy dissipation seriously affects the carbon fixation efficiency of microalgae; Secondly, thermodynamics and metabolic networks are discussed. The role of thermodynamics in addressing the constraints is explored mainly from the perspective of energy conversion mechanisms, free energy dissipation mechanisms, framework and methods. Metabolic networks are studied using sampling methods based on thermodynamic systems and metabolic engineering based on a systems perspective; Thirdly, the key supporting technologies and biological intrinsic characteristics are reviewed from an interdisciplinary perspective, and the researches on metabolic networks based on thermodynamic constraints are given; Finally, challenges are summarized to provide a basis and direction for future research. Highlights: The mechanism of efficient carbon fixation by microalgae is revealed. New methods for improving carbon fixation efficiency by microalgae are proposed. Cross-over researches on the metabolic network are reviewed.